Influenza vaccine effectiveness to prevent influenza-related hospitalizations and serious outcomes in Canadian adults over the 2011/12 through 2013/14 influenza seasons: A pooled analysis from the Canadian Immunization Research Network (CIRN) Serious Outcomes Surveillance (SOS Network). Issue 16 (12th April 2018) - Nichols, Michaela K.; Andrew, Melissa K.; Hatchette, Todd F.; Ambrose, Ardith; Boivin, Guy; Bowie, William; Chit, Ayman; Dos Santos, Gael; ElSherif, May; Green, Karen; Haguinet, Francois; Halperin, Scott A.; et al.
Abstract: Background: Ongoing assessment of influenza vaccine effectiveness (VE) is critical to inform public health policy. This study aimed to determine the VE of trivalent influenza vaccine (TIV) for preventing influenza-related hospitalizations and other serious outcomes over three consecutive influenza seasons. Methods: The Serious Outcomes Surveillance (SOS) Network of the Canadian Immunization Research Network (CIRN) conducted active surveillance for influenza in adults ≥16 years (y) of age during the 2011/2012, 2012/2013 and 2013/2014 seasons in hospitals across Canada. A test-negative design was employed: cases were polymerase chain reaction (PCR)-positive for influenza; controls were PCR-negative for influenza and were matched to cases by date, admission site, and age (≥65 y or <65 y). All cases and controls had demographic and clinical characteristics (including influenza immunization status) obtained from the medical record. VE was estimated as 1-OR (odds ratio) in vaccinated vs. unvaccinated patients × 100%. The primary outcome was VE of TIV for preventing laboratory-confirmed influenza-related hospitalization; secondary outcomes included VE of TIV for preventing influenza-related intensive care unit (ICU) admission/mechanical ventilation, and influenza-related death. Results: Overall, 3394 cases and 4560 controls were enrolled; 2078 (61.2%) cases and 2939 (64.5%) controls were ≥65 y. Overall matched, adjusted VE was 41.7% (95% Confidence Interval (CI): 34.4–48.3%); corresponding VE in adults ≥65 y was 39.3% (95% CI: 29.4–47.8%) and 48.0% (95% CI: 37.5–56.7%) in adults <65 y, respectively. VE for preventing influenza-related ICU admission/mechanical ventilation in all ages was 54.1% (95% CI: 39.8–65.0%); in adults ≥65 y, VE for preventing influenza-related death was 74.5% (95% CI: 44.0–88.4%). Conclusions: While effectiveness of TIV to prevent serious outcomes varies year to year, we demonstrate a statistically significant and clinically important TIV VE for preventing hospitalization and other serious outcomes over three seasons. Public health messaging should highlight the overall benefit of influenza vaccines over time while acknowledging year to year variability. ClinicalTrials.gov Identifier : NCT01517191.